2017
DOI: 10.2118/181347-pa
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Characterization of Suspension of Hollow Glass Beads

Abstract: Summary Hollow glass spheres (beads) are widely used as density and rheological modifiers for various oil and gas process fluids, particularly cement. One of the primary uses is to achieve lightweight slurries with good mechanical properties of the set cement. This paper discusses a concentrated, yet pumpable, suspension of these spheres for offshore cementing applications. Providing the lightweight spheres in a liquid suspension eliminates the risks associated with dry blending these materials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A lack in the literature is also observed when it comes to CMC interaction with glass spheres. Glass spheres are also used as a component in oil-gas fluids applications, mainly in cement (Lumsden et al 2017). A few studies tried to better understand the interactions of the glass spheres (or beads), combined with charge-stabilizing agents in both aqueous and non-aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…A lack in the literature is also observed when it comes to CMC interaction with glass spheres. Glass spheres are also used as a component in oil-gas fluids applications, mainly in cement (Lumsden et al 2017). A few studies tried to better understand the interactions of the glass spheres (or beads), combined with charge-stabilizing agents in both aqueous and non-aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, several studies have been conducted to investigate the properties of various lightweight cement recipes. , However, laboratory findings and field applications have shown that many lightweight cement slurries have increased wait-on-cement (WOC) times and low early-age strength, increasing the chances of gas migration and delaying post-cementing operations, such as cement bond logging. , …”
Section: Introductionmentioning
confidence: 99%